2021
DOI: 10.1007/s11948-021-00338-1
|View full text |Cite
|
Sign up to set email alerts
|

Touching at a Distance: Digital Intimacies, Haptic Platforms, and the Ethics of Consent

Abstract: The last decade has seen rise in technologies that allow humans to send and receive intimate touch across long distances. Drawing together platform studies, digital intimacy studies, phenomenology of touch, and ethics of technology, we argue that these new haptic communication devices require specific ethical consideration of consent. The paper describes several technologies, including Kiiroo teledildonics, the Kissenger, the Apple Watch, and Hey Bracelet, highlighting how the sense of touch is used in marketi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…For example, only a few studies took the relationship and technological context of TMSI into consideration. TMSI can and does occur between people in many relationship contexts and for many relationship-related reasons (e.g., [ 6 , 7 , 91 , 92 ]). Researchers have found that TMSI in a romantic relationship is more common than TMSI with someone who is not one’s romantic partner [ 92 , 93 , 94 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, only a few studies took the relationship and technological context of TMSI into consideration. TMSI can and does occur between people in many relationship contexts and for many relationship-related reasons (e.g., [ 6 , 7 , 91 , 92 ]). Researchers have found that TMSI in a romantic relationship is more common than TMSI with someone who is not one’s romantic partner [ 92 , 93 , 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research on sexting and cybersex suggests that between 25% and 80% of adults report engaging in these forms of TMSIs [ 2 , 3 , 4 , 5 ]. There is very little research on other emerging forms of TMSIs [ 6 , 7 , 8 ]; however, a sizeable minority of participants report having experienced some of these [ 9 ]. Researchers have focused largely on sociodemographic predictors of TMSIs and TMSIs as a predictor of psychosocial outcomes with an emphasis on sexting and negative outcomes (e.g., see [ 8 , 10 ]).…”
Section: Overviewmentioning
confidence: 99%
“…As an approach, autoethnography refers to "research and writing that seeks to describe and systematically analyze (graphy) personal experience (auto) in order to understand cultural experience (ethno)" (Ellis et al, 2011). To this point, scholars have primarily addressed digitally mediated intimacy-broadly defined-from critical cultural (Baym, 2015;Munn, 2012;Ley & Rambukkana, 2021) and ethnographic perspectives (Watson et al, 2021;Hjorth et al, 2018). I contribute to this body of scholarship by sharing my embodied experience-both physical and emotional-during our virtual reality dates.…”
Section: Ragan Glover-rijkse Methodist Universitymentioning
confidence: 99%
“…At the same time, it has been studied how technologies like condoms and teledildonics shape the values we give to sexual intercourse by providing the ability to imbue the act with values like trust. Since condoms “protect” the lovers during intercourse, the decision to use or not to use the condom makes the different trust we have towards the lover visible (Ley & Rambukkana, 2021 ; Liberati, 2020 ).…”
Section: Intimacy In Phenomenology and Postphenomenologymentioning
confidence: 99%